Sistema de clases para el mejoramiento de la pronunciación del idioma inglés - García León, Dajaney Fatima; Villamar Salazar, Margareth Antonella (Machala, Utmachala, 2022)
The purpose of this research is to apply a system of classes based on the use of ludic teaching methods, more specifically games and songs, that contribute to the improvement of pronunciation, focusing on the derivatives of it, such as intonation, rhythm and accentuation. The hypothesis that the researchers put forward is that the application of the lessons with games and songs will improve the pronunciation of the English language. This research is carried out from a quantitative paradigm with a pre-experimental design, with theoretical methods such as historical-logical, analytical-synthetic, hypothetical-deductive and empirical methods such as non-participant observation, experiment and standardized tests, under the pre-test and post-test techniques. The population studied was a total of 27 students from the 4th year of General Basic Education "A" of the "Enrique Castro Aguilar" School in the parish of El Cambio. Once the student's shortcomings had been identified, we assisted with ludic methods, which benefit the teaching and motivation of students through the use of games, plus the correct pronunciation with the use of songs, thus achieving a favourable result for the hypothesis.
La investigación tiene como fin aplicar un sistema de clases basadas en el empleo de métodos lúdicos de enseñanza, específicamente juegos y canciones, los cuales contribuyan al mejoramiento de la pronunciación, enfocándose en los derivados de la misma, tales como entonación, ritmo y acentuación. La hipótesis que las investigadoras plantean es que la aplicación de las clases sea con juegos y canciones mejorará la pronunciación del idioma inglés. Esta investigación se realiza desde un paradigma cuantitativo con un diseño preexperimental, con métodos teóricos como histórico-lógico, analítico-sintético, hipotético-deductivo y; métodos empíricos como observación no participante, experimento y pruebas estandarizadas, bajo la técnicas de pre-test y post-test. Se estudia a una población total de 27 estudiantes pertenecientes al 4to año de Educación General Básica del paralelo “A” de la Escuela “Enrique Castro Aguilar” ubicado en la parroquia El Cambio. Una vez visto las carencias presentadas en el alumnado se asistió con métodos lúdicos, que beneficia la enseñanza y motivación de los estudiantes mediante la utilización de juegos, más la correcta pronunciación por medio de canciones, logrando así un resultado favorable a la hipótesis.
Keywords: METODO LUDICO; PRONUNCIACION; ENTONACION; ACENTUACION; RITMO; SISTEMA DE CLASE; MEJORAMIENTO